Legality of bringing to administrative responsibility for an offense under Art. 130 Code of Ukraine on Administrative Offenses: retrospective analysis - K. O. Chyshko (Bulletin of Kharkiv National University of Internal Affairs)
The provisions of a number of legislative acts have been analyzed in detail, as a result of which driving under the influence of alcohol, drugs or other intoxicants or under the influence of drugs that reduce attention and speed of reaction is recognized as not an administrative but a criminal offense. Some intermediate conclusions have been made. Driving under the influence of alcohol, drugs or other intoxicants or under the influence of drugs that reduce attention and speed of reaction, in the period from July 1, 2020 to March 17, 2021: 1) was recognized not as an administrative offense, but as a criminal offense; 2) detection, termination and documentation of such a criminal offense was carried out mainly by patrol police officers, and not by investigators, as required by current criminal procedure legislation; 3) a report on an administrative offense and other administrative-procedural documents were drawn up upon the fact of committing a criminal offense; 4) the prosecution of a person did not take place as a result of a pre-trial investigation, but within the framework of proceedings in cases of administrative offenses.